2023
DOI: 10.1002/jcu.23463
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of multimodal ultrasound strategies in the differentiation of non‐mass‐like breast lesions

Abstract: Purpose The study aims to assess the diagnostic performance of convention ultrasound (US), Angio PLUS microvascular US imaging (AP), and shear‐wave elastography (SWE) in differentiating malignant and benign non‐mass‐like (NML) breast lesions. Methods Sixty patients aged 21–70 years with 60 NML lesions were recruited. All patients were examined by conventional US, AP, and SWE. According to the pathological results, the performances of the multimodal US strategies were analyzed, while the diagnostic efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[ 14 ] Wang F et al explored the combined application of SWE and a novel blood flow imaging technique called Angio PLUS microvascular US imaging for diagnosing breast non-mass lesions and found an accuracy of 78.3% to 88.3%. [ 27 ] These studies indicated that sonoelastography played a good complementary role on conventional US.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Wang F et al explored the combined application of SWE and a novel blood flow imaging technique called Angio PLUS microvascular US imaging for diagnosing breast non-mass lesions and found an accuracy of 78.3% to 88.3%. [ 27 ] These studies indicated that sonoelastography played a good complementary role on conventional US.…”
Section: Discussionmentioning
confidence: 99%